Immune Characteristics of IgA Nephropathy With Minimal Change Disease - Li, Huixian; Lu, Wanhong; Li, Haiyun; Liu, Xiaoling; Zhang, Xue; Xie, Liyi; Lan, Ping; Yu, Xiaoyang; Dai, Yinjuan; Xie, Xinfang; Lv, Jicheng (Frontiers in Pharmacology, 2021)
Background: IgA nephropathy (IgAN) has a high degree of heterogeneity in clinical and pathologic features. Among all subsets of IgAN, the pathogenesis of IgAN with minimal change disease (MCD-IgAN) remained controversial. Methods: We analyzed the clinical and pathological characteristics of MCD-IgAN patients in a retrospective cohort. Patients diagnosed with IgAN, excluding MCD-IgAN were randomly selected as controls. Levels of plasma galactose deficient IgA1(GdIgA1), IgG autoantibodies against GdIgA1, GdIgA1 deposition in the glomerulus, as well as inflammatory reactivity of circulating poly-IgA complexes to cultured mesangial cells were evaluated. Results: Patients with MCD-IgAN had significantly higher levels of proteinuria and eGFR, lower levels of albumin and urine blood cells, as wells as milder histological lesions by light microscope compared to IgAN patients, which bears a resemblance to MCD. Lower levels of GdIgA1 (3.41±1.68 ug/mL vs. 4.92±2.30ug/mL, p=0.009) and IgG anti-glycan autoantibodies (23.25+22.59 IU/mL vs. 76.58+71.22 IU/mL, p<0.001) were found in MCD-IgAN patients than those in IgAN controls. Meanwhile, weaker fluorescence intensities of both IgA and GdIgA1 were observed in glomerulus of MCD-IgAN patients compared to those in IgAN patients. Furthermore, poly-IgA1 complexes from MCD-IgAN patients induced weaker inflammatory effects on cultured mesangial cells than those from IgAN patients in vitro. Conclusions: The results demonstrated that MCD-IgAN cases represent a dual glomerulopathy, namely mild IgAN with superimposed MCD, which furthermore providing substantial evidence for the corticosteroids therapy in MCD-IgAN patients as the guidelines recommended.